Analysis of DevOps Implementation on Project Audit System Development in a Construction Company - Denny Jean Cross Sihombing (SEAN Institute, 2023)
This research aims to develop a construction project audit system using DevOps methodology to improve efficiency and accuracy in construction project management. The research stages include Assessment, Plan, Develop, Deliver, Operate, and Evaluation. The results showed that the project audit system was successfully developed and operated for the past two years. System performance evaluation revealed that the average response time of the system was 120 m/s, with system availability reaching 99.8%. The project audit data has an accuracy rate of 99%, which confirms the reliability of the information generated by this system. The data analysis tool performed optimally and generated audit reports in an average of 20 seconds per report. The system contributes positively to addressing challenges in the construction industry by improving efficiency and accuracy in construction project management and audit supervision. Future research can explore the integration of the latest technologies, such as artificial intelligence and cloud computing, in project audit systems and measure their impact on actual construction projects.